2017
DOI: 10.1111/vcp.12443
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatine kinase isoenzymes and macroenzymes in dogs with different neurologic diseases

Abstract: The results of this study suggest that CK-BB is released by neurons damaged by inflammatory or degenerative conditions or due to compressive effects of SOL. However, the neurologic diseases cannot be differentiated based on CK-BB or Macro-CK2 activities, unless further studies allow the definition of diagnostic thresholds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This corroborates literature data showing that azotemia is an uncommon finding, despite elevated frequencies of renal pathologies in CanL [58]. Creatinine is a by-product of CK, whose levels are reduced in dogs with LCan [59]; therefore, we suggest that this bias of azotemia diagnosis in advanced CanL results from sub-concentration of creatinine and might lead to kidney disease underdiagnoses. It has been stressed in the literature that the active infection by L. infantum and CanL progression relates with immune complex-mediated disease [60], which plays an important role in the pathophysiology of diverse clinical manifestations, including immune-mediated hemolytic anemia, glomerular lesions and renal failure [38,61].…”
Section: Discussionsupporting
confidence: 91%
“…This corroborates literature data showing that azotemia is an uncommon finding, despite elevated frequencies of renal pathologies in CanL [58]. Creatinine is a by-product of CK, whose levels are reduced in dogs with LCan [59]; therefore, we suggest that this bias of azotemia diagnosis in advanced CanL results from sub-concentration of creatinine and might lead to kidney disease underdiagnoses. It has been stressed in the literature that the active infection by L. infantum and CanL progression relates with immune complex-mediated disease [60], which plays an important role in the pathophysiology of diverse clinical manifestations, including immune-mediated hemolytic anemia, glomerular lesions and renal failure [38,61].…”
Section: Discussionsupporting
confidence: 91%
“…Overexpression of miR-519b-3p suppressed the invasion and proliferation of CRC cells. Creatine kinases (CKs) are isoenzymes that catalyze the reversible transfer of phosphate groups from phosphocreatine to ADP, generating ATP and creatine (Paltrinieri et al, 2017). Different types of CKs are found in the cytosol and mitochondria of cells.…”
Section: Introductionmentioning
confidence: 99%
“…As the stability of coronary plaques decreases, myocardial ischemia intensifies and increases the risk of myocardial infarction, and the substances reflecting myocardial damage increase significantly. Studies have found that vaspin levels are significantly negatively correlated with myocardial injury markers such as creatine kinase isoenzymes, which in turn participate in the occurrence and progression of CHD (19). Visfatin is not only a fat factor but also an important proinflammatory factor in the body.…”
Section: Discussionmentioning
confidence: 99%